The Economics of Product Patents - Waterson, Michael (American Economic Review, 1990)
This paper develops a model of product patents in which the patent changes the nature of market entry behavior rather than preventing entry entirely. The model incorporates three levels of action, namely, the innovator's patenting decision, the potential entrant's location decision, and possible court action. The analysis demonstrates how the characteristics of the patents system and the enforcement framework can influence rivals' variety choices and, thus, the market equilibrium. It also considers how the system can, in principle, be adjusted to improve social welfare. Copyright 1990 by American Economic Association.